Literature Review of Spiritual Care in Islamic Cultural Perspective - Henie Kurniawati; Sofia Retnowati; Bagus Riyono; Widyawati Widyawati (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This article aims to literature review regarding spiritual care in Islamic culture perspective. Systematic review is done to support knowledge regarding spiritual care. Literature studies from 2007 to 2017 are identified narratively and reviewed critically in Islamic cultural perspectives. The method for literature analysis is using eight steps from Walker and Avant. The findings of this review stated that spiritual care is a dynamic activity to integrate physical, psychological, social, and spiritual aspects. Spiritual care takes the form of spiritual service that is done dynamically and integratively based on divine and human values especially Islamic cultural values. The main services include caring for the sick, identifying spiritual needs, and increasing spiritual well-being. The implications of the findings are to help building policies in nursing and to help nurses in developing positive attitude in applying spiritual care. The conclusion of this literature review produces a comprehensive definition regarding spiritual care and supports spiritual care competency in health in Islamic cultural perspective.